Olfactory responses of Habrobracon hebetor (Hymenoptera: Braconidae) to carob moth, Ectomyelois ceratoniae (Lepidoptera: Pyralidae) and its host plant - Fatemeh Shafaghi; A. Avand-Faghih; Seyed Hossein Goldansaz (نامه انجمن حشره‌شناسی ایران, 2020)
Semiochemicals play a key role on host selection of parasitoids. Responses of parasitoid wasp, Habrobracon hebetor (Say), to volatiles emitted from Ectomyelois ceratoniae Zeller larva, pomegranate as its host plant and herbivorous induced plant volatiles (HIPVs) were investigated using a Y-shaped olfactometer. The results showed that the last larval instar of E. ceratoniae, its feces, the mechanically damaged pomegranates and the infested pomegranates by larva were attractive for the parasitoid wasp. The volatiles of E. ceratoniae larvae and its feces were extracted by solid phase micro-extractionand then identified by GC-MS. Respectively, 40 and 45 components were identified in headspaces of the last larval instar of E. ceratoniae and its feces. The major identified components were1-Pentadecane, Nonanal, Octanal, Decanal, Hexanal and Limonene. More studies are needed to identify HIPVs and also to evaluate the behavioral activity of identified volatiles.